Anti-inflammatory activity of flavonols via inhibiting MAPK and NF-κB signaling pathways in RAW264.7 macrophages - Ruting Zhong; Lingchao Miao; Haolin Zhang; Lihua Tan; Yuxin Zhao; Yanbei Tu; Miguel Angel Prieto; Jesus Simal-Gandara; Lei Chen; Chengwei He; Hui Cao (Current Research in Food Science, 2022)
Fisetin (Fis), quercetin (Que), and myricetin (Myr) are flavonols with similar structure but different number of hydroxyl groups. The present research focused on the anti-inflammatory effect of these three flavonols in lipopolysaccharide-stimulated RAW264.7 cells. The number and site of hydroxyl group in flavonols obviously affected their anti-inflammation activity. These flavonols suppressed the overproduction of nitric oxide. Fis showed the best activity with an inhibition rate of 52% at 20 μM. Moreover, the flavonols reduced the levels of ROS, TNF-α, and IL-6. The mechanistic study showed that they inhibited the activation of NF-κB and MAPK pathways by suppressing the phosphorylation of IκBα, p65, JNK, ERK, p38, MEK, and reducing the nuclear translocation of NF-κB p65. In addition, the metabolism of the flavonols was examined. The results indicated that Fis was both methylated and glucuronidated. Que and Myr were mainly transformed into methylated products. This study highlights the anti-inflammatory activity of flavonols, particularly Fis, which has the potential for the prevention or treatment of inflammation as an adjuvant medicine or food additive.